Simulation and analysis of improved direct torque control of switched reluctance machine - Alexander Krasovsky (Institute of Advanced Engineering and Science, 2020)
Direct torque control of electric machines widely used in modern electric drives. Switched reluctance machines (SRM) are different from traditional electric machines, so we cannot apply well-known technical solutions to them. Simulation can provide a powerful approach for investigating the control of switched reluctance machines, and Matlab / Simulink allows it successfully implemented. This paper presents a description of the model and the simulation results of the proposed new algorithms for direct control of the instantaneous torque of SRM in the motor and braking modes. In comparison with the known control algorithms, the proposed algorithm uses one common for all phases relay regulator with a smaller number of switching thresholds and, therefore, it has greater reliability and is easier to set up.